Detection of Single Nanoparticles inside a Single Terahertz Resonator. Issue 11 (17th August 2022) - Bahk, Young-Mi; Kim, Kyoung-Ho; Ji, Gangseon; Ahn, Kwang Jun; Kim, Dai-Sik; Park, Hyeong-Ryeol
Abstract : With the rapid advancement of 5G/6G communications using millimeter wavelengths, the concomitant usage of these long wavelength radiation for remote sensing and monitoring of biological and chemical agents is anticipated. However, the ability to detect and identify these agents with sizes ranging from nanometers to microns is hampered by its millimeter wavelength, which drastically reduces the interaction cross‐section. Herein, it is reported that single gold nanoparticles (NPs) drop‐casted on the nanoresonator can be observed by monitoring the far‐field transmitting spectra of individual terahertz (THz) nanoresonators, which enhance the electric field hundreds of times on the nanoscale. Despite the enormous mismatch in length scales, full‐wave 3D numerical modeling of the single THz nanoresonator is also performed to interpret the experimental results, indicating the possibility to turn off the resonance using only one NP embedded in the hotspot of the nanoresonator. Such NP detection becomes the most sensitive when the particle, whose size is comparable to the gap width, is tightly fitted into the nanoresonator. This work unveils the potential associated with refractive index sensing and hyperspectral absorption spectroscopy for detecting and fingerprinting ultra‐low density of bio/chemical molecules such as viruses, lipid vesicles, and explosives. Abstract : Single gold nanoparticles (NPs) drop‐casted on the nanoresonator can be observed by monitoring the far‐field transmitting spectra of individual terahertz (THz) nanoresonators, which enhance the electric field hundreds of times on the nanoscale. Such nanoparticle detection becomes the most sensitive when the particle, whose size is comparable to the gap width, is tightly fitted into the hotspot of the nanoresonator.